Awareness and understanding of sustainable development among lecturers in Universiti Utara Malaysia - Hamdan, Nur Shuhaddah; Ashari, Hasbullah (2016)
This review is about awareness and understanding of sustainable development among lecturers in University Utara Malaysia. Sustainable development is a vast, complicated issue to comprehend. The sustainable development is so difficult to understand is that the only person think about it are considering the environmental impact rather, it covers all the industrial, technology, science and politics impact.Sustainable development is a critical issue in our and other country.This matter relevant at this point when global warming issues arise. The negative impact of current development which contributes to environment degradation such as extinction of forest will impact the sustainable development.This project will focus on providing awareness and understanding of sustainable development. It will operate among the lecturers from different educational backgrounds study in UUM. The purpose of this project is to identify the understanding emerging concepts and the fundamental values behind various different interpretations on sustainable development.The awareness and understanding of sustainability development is needed to improve the knowledge by means of referring the needs and pertinent problems as expressed by the lecturer in University Utara Malaysia.The awareness and understanding of sustainable development must be clearly identified and understood for the need of future generation.